2015
DOI: 10.12740/pp/22934
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Polish version of the brief version of Kutcher Adolescent Depression Scale – assessment of depression among students

Abstract: Validation of Polish version of KADS in a group of students aged 18-24 years has shown its high reliability and content validity. Further studies should be focused on the assessment of the questionnaire criterion validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
1
13
2
4
Order By: Relevance
“…In this study, the prevalence of depression was 1.6% in children and adolescents aged 6 to 18 years old, which is consistent with Young study reporting the prevalence of depression as 1.32% (11). However, another study found that depression was more common in adolescents of the 12 -18 age group (21). This greatly differs from the results of our study, which is probably due to the use of the semistructured diagnostic questionnaire, K-SADS-PL.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the prevalence of depression was 1.6% in children and adolescents aged 6 to 18 years old, which is consistent with Young study reporting the prevalence of depression as 1.32% (11). However, another study found that depression was more common in adolescents of the 12 -18 age group (21). This greatly differs from the results of our study, which is probably due to the use of the semistructured diagnostic questionnaire, K-SADS-PL.…”
Section: Discussioncontrasting
confidence: 99%
“…cigarette)". Depression was assessed using the shortened version of the Kutcher Adolescent Depression Scale (KADS) by Brooks et al (2003) in its Polish adaptation (Mojs et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The scale includes six statements, each of which is rated on a five-point scale, from 0 = "never or almost never" to 3 = "always". As per Mojs et al (2015), an overall score equal to or greater than six (≥6) indicates the likelihood of depression. The reliability of the scale was adequate (α = 0.82).…”
Section: Methodsmentioning
confidence: 99%
“…We validated the test for the population of youth aged 12–25 with very good psychometric properties. Furthermore, we found that validation parameters of the Polish version corresponded to those obtained during validation of the original version [ 27 ]. There were other scales available such as the Montgomery-Asberg Depression Rating Scale (MADRS) or Hamilton Rating Scale for Depression (HAM-D), which could be applied but they were time-consuming and could be administered only by trained and experienced clinicians [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%